2022
DOI: 10.1111/dth.15903
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of topical hyaluronic acid for skin quality and signs of skin aging: From literature review to clinical evidence

Abstract: Skin aging goes beyond a chronological process and also results from extrinsic factors referred to as the exposome. Hyaluronic acid (HA) is an important component of the extracellular matrix, with loss starting at 25 years old. While many studies of HA concern topical use, few literature reviews only address the use of topical HA in dermatology. This review describes the different characteristics of HA-containing cosmeceuticals, with a focus on skin aging and the impact of exposome factors on HA synthesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 38 publications
(127 reference statements)
0
15
0
Order By: Relevance
“…These products may be useful for helping to maintain healthy, youthful-looking skin and may be suitable for people of all skin types and concerns. 28,29 HA has been shown to be effective in improving the quality of facial skin, particularly when used in consecutive treatments spaced a few weeks apart. This may be due to the viscoelastic properties of HA, which help to improve skin elasticity and firmness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These products may be useful for helping to maintain healthy, youthful-looking skin and may be suitable for people of all skin types and concerns. 28,29 HA has been shown to be effective in improving the quality of facial skin, particularly when used in consecutive treatments spaced a few weeks apart. This may be due to the viscoelastic properties of HA, which help to improve skin elasticity and firmness.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has suggested that HA may have beneficial effects when used topically in dermatological practice, although more studies are needed to fully understand its potential effects. 28 There is a growing body of evidence suggesting that HA is well-tolerated and effective when used in combination with various facial rejuvenation procedures, such as botulinum toxin type A, photodynamic therapy, fractional CO 2 laser skin resurfacing, fillers, microneedling, and chemical peeling. Clinical studies have generally found that HA-based cosmeceuticals, which are skin care products that contain HA and other active ingredients, can help to improve skin hydration, rejuvenation, and healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A serum aimed at both groups (Neovadiol meno 5 bi‐serum; Laboratoires Vichy, France) contains VVMW, proxylane, cassia extract, vitamins B3, C, and E, omegas 6 and 9, LHA and glycolic acid. Additional key ingredients are HA in the perimenopause creams (Neovadiol redensifying day cream [cream A] and night cream [cream B]) for its hydration properties; 27 and omegas 3,6 and 9 in the creams for women during the menopause (Neovadiol replenishing day cream [cream C] and night cream [cream D]) to replenish lipid loss.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the epidermal HA content decreases from 0.03% in 19–47‐year‐old women down to 0.015% in 60‐year‐old women 11 . Therefore, it is necessary to supplement HA to maintain skin hydration and elasticity 12 . As a natural moisturizing factor (NMF), not only does HA form hydrogen bonds with water, but also it controls water mobility by interacting with AQP3 13 .…”
Section: Introductionmentioning
confidence: 99%